Interaction of phage and gentamicin combinations in Pseudomonas aeruginosa and Staphylococcus aureus polymicrobial biofilms - Akturk, Ergun (2019)
Bacteria-associated polymicrobial biofilms are sessile microbial aggregates of different species adhered to surfaces and encased in a self-produced extracellular polymeric matrix, which shows a high degree of tolerance/resistance to disinfection by chemicals, antibiotics, and to the human immune system. Pseudomonas aeruginosa and Staphylococcus aureus are versatile bacterial pathogens and common etiological agents of several chronic infections, namely otitis media, oral infections, surgical-side infections, diabetic foot ulcers, and cystic fibrosis. In this study we aimed at assessing the efficacy of phages (vB_PaM_EPA1) to control P. aeruginosa and S. aureus polymicrobial biofilms, alone and combined with Gentamicin (GEN). The phage and the antibiotic were simultaneously or sequentially combined and added to 48 hours-old biofilms. After 24 hours treatment the number of viable cells were enumerated by CFU counting and observed under confocal laser microscopy with fluorescence probes. Probes were designed to specifically target the bacterial species and consists of a recombinant tail fibre protein P. aeruginosa-specific fused to mCherry (mCherry+TFP) and a cell wall binding domain of a phage endolysin, S. aureus specific, fused to GFP (GFP+CBD). Results showed that phage-drug combinations greatly reduced the number of P. aeruginosa viable cells, ranging from 4.06 to 6.32 orders-of-magnitude. The best treatment outcome was observed with sequential treatment by combing first EPA1 and then GEN. Overall, our results support the phenomenon that combination of phages and antibiotics are very effective against P. aeruginosa in dual-species biofilms when applied sequentially, and this constitutes a good strategy to control biofilm-associated infections.